Measurement of HRTF/HRIR for in-ear and hearing aid microphones with respect to the change of distance of the sound source - Tan, Boon Siang (2018)
Head Related Transfer Function (HRTF) describes the characteristic and transformation of sound due to the effect of the head and torso as well as the external ears that provide spatial cues to the human auditory system to localize sound. It has been widely used in the virtual sound spatialization. But the generic form that is obtained from the manikin provides inadequate cues for the human subject to localize sound due to the physical differences of every individual. The HRTF that is unique to each individual is acquired to enable accurate sound lateralization, but it is also a laborious task and is very time consuming. Therefore, the more efficient acquisition method such as the fast and unconstrained continuous HRTF measurement system has been proposed. Due to the dynamic measurement method, the conventional in the ear type microphone design is not robust enough against the constant movement during the measurement and may cause interruption if it is not properly fitted onto the ear. In this dissertation, the high sensitivity and low noise HRTF acquisition microphone that can be securely wear on the ear is developed. With the newly developed microphone that coupled on the fast and unconstrained continuous HRTF measurement system, the measurement is performed on the Kemar ears including the near field distance dependent HRTF. Besides, the influence of the VR head gear that is equipped with the measurement system as well as the effect of the misalignment of head and torso due to the unconstrained movement have also been evaluated.